A Imutabilidade da causa de pedir e o fato superveniente no processo civil brasileiro - Guibo, Antonio Rugero (2005)
The present work is related to the study of the tension between, on one side, the necessity of the steadiness of the dispute by which the claimant is not allowed to modify the cause of action, and on the other side, the recognition that the new facts have to be taken into consideration by the judge, thus interfering on the judgement of the lawsuit. The main goal is to examine the origin and historic evolution of the cause of action as the identifying element of the lawsuit, to arrive at the study of the steadiness of the dispute theme in the comparative law, as well as in the Brazilian statutory law. Further, the problem is analyzed as the way it is presented in the current civil proceeding s system, where a parallel is made with a very similar but not identical institute, the contingency principle. Also the different implications of the preclusive characteristic of the res judicata are analysed, if it is related to a new fact which benefits the claimant and the defendant, as well as the relation of the steadiness theme of the lawsuit with the congruency and causality principles. Finally, the question is posed from the appeal theory point of view. The purpose of the present work is to seek a systematization of the concepts involved which allows the harmonization of the rules which will take to the steadiness of the lawsuit, due to the necessity of dealing with the new fact. Without prejudice to the discussion in respect to the theoretical aspects, it is intended not to lose track of the practical interest of seeking criteria capable of making operable, coherent and efficient the group formed by the above mentioned institutes, with the view to delimitate the exact reach of the immutability of the cause of action in the Brazilian civil proceeding s system, due to the appearance of new facts.